A narrative review on sexual wellbeing and dysfunctions: Research in the past 15 years - Neena Sawant; Sreelakshmi Vaidyanathan; T S Sathyanarayana Rao; Suparna Telang (Indian Journal of Psychiatry)
Background: Psychosexual health is an important aspect of mental and physical wellbeing. Though Indian culture has a rich history of sexuality, over the years, our population has been reticent in talking about the same. With the advent of technology and new legislations protecting the rights of LGBTQIA population, awareness is also on the rise. Methods: This review focuses on research published by Indian authors over the past 15 years, with search of databases like PubMed, Scopus, Google Scholar, and Litmaps to include original articles and case reports. Results: Most studies focus on male sexual dysfunctions. Some emerging research showed promise in female sexual dysfunctions, the elderly, and the LGBTQIA population. The majority of research in sexual health continues to concentrate on dysfunctions, primarily prevalence, associations, or risk factors. Several studies investigated various medical/psychiatric comorbidities associated with sexual dysfunctions. A few studies have explored management strategies as well. Conclusion: This review highlights the need for a more holistic approach to management to sexual health issues. It further underscores the importance of grassroots-level initiatives working on improving the training of all medical practitioners and postgraduate students, increasing the availability of services for sexual disorders, promoting sexual health research in areas with gaps, and raising awareness in the general population.